Penerapan Perma Nomor 5 Tahun 2014 Tentang Pidana Tambahan Uang Pengganti Dalam Tindak Pidana Korupsi - Rahma Noviyanti (Nagari Law Review, 2019)
Corruption in Indonesia is currently a serious crime that is carried out systematically and has a broad impact on people's lives. State’s assets which should be used for development in order to benefit the society, are used for personal interests. Through the Corruption Law, the State tried to eradicate corruption and restore assets that have been corrupted. The restoration is endeavored by the application of additional punishment in the form of payment of substitute money. In order to optimize the implementation of the payment, the Supreme Court has issued a regulation of Substitute Money to provide the same understanding for the Law Enforcers, specifically Judges, in the imposition of the regulation on Defendants of Corruption. The problems in this research are: How is the implementation of Supreme Court Regulation on Substitute Money in the verdict to the defendants of corruption. The method used in this research is sociological juridical method. The type of the research is descriptive by using primary data and secondary data. The results of the study revealed The Judges have implemented some of the clauses of the regulation on making the decision, however the implementation have not evenly stated on each verdict